2010
DOI: 10.1186/1475-2875-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PermaNet 3.0 a deltamethrin-PBO combination net against Anopheles gambiae and pyrethroid resistant Culex quinquefasciatus mosquitoes: an experimental hut trial in Tanzania

Abstract: BackgroundCombination mosquito nets incorporating two unrelated insecticides or insecticide plus synergist are designed to control insecticide resistant mosquitoes. PermaNet 3.0 is a long-lasting combination net incorporating deltamethrin on the side panels and a mixture of deltamethrin and synergist piperonyl butoxide (PBO) on the top panel. PBO is an inhibitor of mixed function oxidases implicated in pyrethroid resistance.MethodAn experimental hut trial comparing PermaNet 3.0, PermaNet 2.0 and a conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 34 publications
9
121
1
Order By: Relevance
“…This efficacy has also been observed in Ethiopia [9] and Cote d’Ivoire [18]. A similar study conducted in Muheza, Tanzania found that the personal protection rates for PermaNet® 3.0 and PermaNet® 2.0 washed 20 times were 71 and 73%, respectively [17]. The cause of these variations in the personal protection rate between and within the two PermaNet brands done in Tanzania are still not well understood.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…This efficacy has also been observed in Ethiopia [9] and Cote d’Ivoire [18]. A similar study conducted in Muheza, Tanzania found that the personal protection rates for PermaNet® 3.0 and PermaNet® 2.0 washed 20 times were 71 and 73%, respectively [17]. The cause of these variations in the personal protection rate between and within the two PermaNet brands done in Tanzania are still not well understood.…”
Section: Discussionmentioning
confidence: 63%
“…These findings indicate that PermaNet® 2.0 and improved PermaNet® 3.0 (with PBO) are advanced tools for protection against resistant populations of An. gambiae mosquitoes [8, 17, 37]. This efficacy has also been observed in Ethiopia [9] and Cote d’Ivoire [18].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Each insecticide has a distinct spectrum of insecticidal outcomes on mosquitoes, which imply that LLINs based on different insecticides may have different effects on mosquito vectors. Previous studies have suggested that LLINs elicited very low level of deterrence against susceptible mosquito vectors and were effective because they did not allow mosquitos to feed on the user [19,[21][22][23][24].…”
Section: An Operational Description Of Insecticides Used In Llinsmentioning
confidence: 99%